Complexes with macrocyclic ligands, III: Pentaco-ordinate metal complexes with 1,4,7,10,12,12 - hexamethyl -1,4,7,10- tetraazacyclotridecane, 1,4,8,11-tetramethyl-1,4,8,11-tetraazacyclotetradecane and 1,4,5,8,11,12- hexamethyl-1,4,8,11-tetraazacyclotetradecane - Rudolf Buxtorf; Willi Steinmann; Thomas A. Kaden (CHIMIA)
The synthesis and complexation with Co(II), N (II) and Cu(II) of the three title compounds is described. The complexes formed by these ligands exhibit spectral properties, which are best explained by assuming pentaco-ordination of the metal ion. Equilibrium studies with SCN- and pH-titrations indicate that beside the four amino groups of the macrocycle a water molecule is also co-ordinated. The unexpected structures are kinetically determined.